THE MORPHOLOGICAL AND SEMANTIC STRUCTURE OF GEORGIAN AND ABKHAZ TOPONYMS IN SAMURZAQANO - Monika Khobelia (International Journal of Innovative Technologies in Social Science, 2025)
The given article presents an analysis of the morphological and semantic structure of the Georgian and Abkhaz toponyms of Samurzaqano. The relevance of the topic is determined by the following circumstance: specifically, after 1993, the toponymic situation in this region changed radically: all toponyms of Georgian origin were prohibited, and Abkhaz names invented by separatists - names that had never existed before or were unofficial versions of Georgian toponyms adapted into the Abkhaz language—became dominant.Our aim is to provide a detailed morphological analysis of the Georgian and Abkhaz toponyms from the pre-occupation period of the Samurzaqano region in Abkhazia. The research is based on toponyms recorded by the well-known Georgian researcher Paata Tskhadaia.It was found that the majority of microtoponyms in the studied area are entirely Georgian in structure: they are Georgian, or Mingrelian, or contain Mingrelian roots, bases, and affixes used as derivational affixes.The second group of toponyms is entirely in the Abkhaz language, and here too, a diverse picture emerges in terms of morphological analysis. Specifically, there are both simple-rooted Abkhaz toponyms and complex-rooted, composite-derived Abkhaz toponyms, in which the morphological and syntactic features characteristic of Abkhaz determinatives and boundary markers are preserved.The examined material clearly shows that the toponyms of Samurzaqano represent a variety of morphological and semantic groups. It is noteworthy that Kartvelian toponyms and derivational affixes are more dominant, and even in Abkhaz roots, Kartvelian derivational affixes are often present.